2017
DOI: 10.5194/bg-14-921-2017
|View full text |Cite
|
Sign up to set email alerts
|

Multi-frequency electrical impedance tomography as a non-invasive tool to characterize and monitor crop root systems

Abstract: Abstract. A better understanding of root–soil interactions and associated processes is essential in achieving progress in crop breeding and management, prompting the need for high-resolution and non-destructive characterization methods. To date, such methods are still lacking or restricted by technical constraints, in particular the charactization and monitoring of root growth and function in the field. A promising technique in this respect is electrical impedance tomography (EIT), which utilizes low-frequency… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 100 publications
(141 reference statements)
1
41
0
Order By: Relevance
“…Depending on the season, roots carry electrical charges as sap composition is variable and sap flows vary in intensity and direction. Wood composition and physical properties also change with root decay, which implies a variation of electrical properties (Martin, 2012;Martin and Günther, 2013;Weller et al, 2006). Very recently, Rao et al (2018) produced an interesting study aiming at understanding bulk electrical conductivity on individual root segments, incorporating the impact of roots in the pedophysical relations to better infer the real soil water content.…”
Section: Noninvasive Measurements and Electricalmentioning
confidence: 99%
“…Depending on the season, roots carry electrical charges as sap composition is variable and sap flows vary in intensity and direction. Wood composition and physical properties also change with root decay, which implies a variation of electrical properties (Martin, 2012;Martin and Günther, 2013;Weller et al, 2006). Very recently, Rao et al (2018) produced an interesting study aiming at understanding bulk electrical conductivity on individual root segments, incorporating the impact of roots in the pedophysical relations to better infer the real soil water content.…”
Section: Noninvasive Measurements and Electricalmentioning
confidence: 99%
“…These studies showed that the spatial resolution of IP imaging is not sufficient to resolve single roots, but that the root extent can potentially be reconstructed. Interestingly, the frequency dependence of the electrical properties of root signals was also evident in the imaging results (see Weigand and Kemna 2017), providing potential to improve measurement results by careful selection of measurement frequencies. This will be especially helpful in cases where the electrical properties of both soil and root exhibit strong frequency dependence.…”
Section: Imaging Of the Induced Polarization Response Of Root Systemsmentioning
confidence: 79%
“…Time‐lapse IP imaging is required to spatially and temporally differentiate root structure and activity. So far, distinct polarization signatures of non‐woody crop roots have been reconstructed from spectral IP 2D or 3D images in controlled laboratory experiments on root systems embedded in aqueous solutions (Weigand ; Weigand and Kemna , ). These studies showed that the spatial resolution of IP imaging is not sufficient to resolve single roots, but that the root extent can potentially be reconstructed.…”
Section: Root Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…EIT is mainly used in animal experiments and tentatively in human clinical research related to digestive, respiratory, and craniocerebral issues [13][14][15][16][17]. In recent years, some researchers have used EIT technology to study soil properties, wood decay, root physiological state, and cold resistance of plants [18][19][20][21][22]. There are few reports on the establishment of regression models for the effect of plant physiological state on EIT parameters.…”
Section: Introductionmentioning
confidence: 99%